2015
DOI: 10.1038/ncomms7377
|View full text |Cite
|
Sign up to set email alerts
|

RB loss in resistant EGFR mutant lung adenocarcinomas that transform to small-cell lung cancer

Abstract: Tyrosine kinase inhibitors (TKIs) are effective treatments for non-small cell lung cancers (NSCLCs) with epidermal growth factor receptor (EGFR) mutations. However, relapse typically occurs after an average of one year of continuous treatment. A fundamental histological transformation from NSCLC to small cell lung cancer (SCLC) is observed in a subset of the resistant cancers, but the molecular changes associated with this transformation remain unknown. Analysis of tumor samples and cell lines derived from res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
488
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 524 publications
(515 citation statements)
references
References 38 publications
26
488
0
1
Order By: Relevance
“…This phenomenon of transformation has been previously reported in case reports and has been confirmed with repeated biopsies in patient cohorts (59,60,68,69). Clinicians must be aware of this possibility in patients receiving targeted therapies who clinically deteriorate.…”
Section: Mechanisms Of Acquired Resistance To Targeted Cancer Therapiesmentioning
confidence: 63%
See 1 more Smart Citation
“…This phenomenon of transformation has been previously reported in case reports and has been confirmed with repeated biopsies in patient cohorts (59,60,68,69). Clinicians must be aware of this possibility in patients receiving targeted therapies who clinically deteriorate.…”
Section: Mechanisms Of Acquired Resistance To Targeted Cancer Therapiesmentioning
confidence: 63%
“…These biopsies have also been very useful to observe the phenotypic and histological changes of the so-called histological transformation from NSCLC to SCLC (1,3,59) and epithelial-to-mesenchymal transition (EMT) (60). EMT consists of the loss of the epithelial morphology of the neoplastic cells that develop into a form that resembles that of mesenchymal neoplasms.…”
Section: Mechanisms Of Acquired Resistance To Targeted Cancer Therapiesmentioning
confidence: 99%
“…The RB tumor suppressor is a major negative cell-cycle regulator that is inactivated in approximately 11% of all human cancers, and nearly 100% of SCLC (24,28). Moreover, activated CDK4/6 promotes G 1 -S traversal by phosphorylating and inactivating RB.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of adenocarcinoma to SCLC in patients with somatic EGFR mutations as the TKI therapy resistance mechanism has previously been reported (15), and the percentage of transformation from adenocarcinoma to SCLC was identified in 14% of cases (7). Analysis of tumor samples and cell lines derived from resistant EGFR mutant patients revealed that RB is lost in 100% of such SCLC transformed cases, but rarely in those that remain NSCLC (16). The gene detection in the present patient following icotinib resistance also revealed RB loss and the appearance of a PIK3CA gene mutation.…”
Section: Discussionmentioning
confidence: 99%